Understanding premenstrual exacerbation: navigating the intersection of the menstrual cycle and psychiatric illnesses - Lin, Jenny; Nunez, Christine; Susser, Leah; Gershengoren, Liliya (Frontiers in Psychiatry, 2024)
Premenstrual exacerbation of an existing psychiatric disorder refers to the worsening of symptoms inherent to the condition during the premenstrual phase. Research consistently indicates that hormonal fluctuations during the menstrual cycle present a unique period of vulnerability for the onset or exacerbation of psychiatric symptoms, impacting diagnosis, risk assessment, and treatment. This review sought to elucidate the phenomenon of premenstrual exacerbation and its impact across a spectrum of psychiatric illnesses, including mood, anxiety, psychotic, obsessive-compulsive, personality, and trauma-related disorders. Despite the expanded research in recent years on premenstrual dysphoric disorder and premenstrual syndrome, premenstrual exacerbation remains underexplored and poorly defined. This review offers significant contributions to the diagnosis and management of psychiatric conditions, advocating for heightened awareness and novel treatment approaches in the context of premenstrual exacerbation.